Jawabanmu

2014-04-26T15:33:06+07:00
Lim   (Sin x - Sin 3x)  = lim    2Cos 2xSin(-x)
x⇒0 (Sin x + Sin 3x)    x⇒0 2 Sin2x C0s (-x))
                               = lim    2 Sin x  Cos 2x
                                  x⇒0 -2Sin 2x Cos x
                               = lim   2(1)Cos 2x
                                  x⇒0 -2(2) Cos x
                               = lim  Cos 2x
                                 x⇒0 -2 Cosx  gan ti x dengan 0 derajat
                               = Cos 0
                                  -2C0s0
                               =  -  1
                                     2